Home / Expert Answers / Other Math / construct-formal-proof-of-validity-using-the-method-of-conditional-proof-assumption-can-be-taken-pa947

(Solved): Construct formal proof of validity using the method of Conditional Proof. Assumption can be taken ...



Construct formal proof of validity using the method of Conditional Proof. Assumption can be taken only from the conclusion pa

Construct formal proof of validity using the method of Conditional Proof. Assumption can be taken only from the conclusion part. Only one assumption is allowed and clearly show where the scope of assumption ends. (Answer Must Be HANDWRITTEN) [4 marks] \( (\mathrm{x})\{(\mathrm{Fx} \cdot \mathrm{Gx}) \supset[\mathrm{Hx} v \sim(\mathrm{Ix} \vee \mathrm{J} \mathrm{x})]\} \) \[ \begin{array}{l} \sim(\exists \mathrm{x})(\mathrm{Fx} . \sim \mathrm{Gx}) \\ \sim(\exists \mathrm{x})[\mathrm{Hx} \cdot \sim(\mathrm{Ix} \cdot \sim \mathrm{Zx})] / \therefore(\mathrm{x})[\mathrm{Fx} \supset(\mathrm{Hx} \equiv \mathrm{Ix})] \end{array} \]


We have an Answer from Expert

View Expert Answer

Expert Answer


We have an Answer from Expert

Buy This Answer $2

Place Order

We Provide Services Across The Globe